Looking at the other side of the coin: The relationship between classical growth and early development theories - Maiju Perälä (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
This paper extends the history of thought narrative on Allyn Young to recognize the close relationship that the classical growth theory has with the early development theory, as Young's externalities-fuelled, cumulative growth process influenced the theoretical thought of the early development theory pioneers, Paul Rosenstein-Rodan and Ragnar Nurkse. The conditions that prevent the development of underdeveloped regions, indivisibilities and inelasticities of supplies and demands, represent the breakdown of the conditions that Young highlights as necessary for self-sustaining growth to occur. Hence, Young's cumulative growth process underlies the view of these early development theorists, though their focus is on the malfunctioning and restarting of this process.
Keywords: B12; B29; B31; 330; classical growth theory; development theory; cumulative growth; externalities; Allyn Young; Paul Rosenstein-Rodan; Ragnar Nurkse; Wachstumstheorie; Entwicklungstheorie